TAC3/TACR3 System Function in the Catadromous Migration Teleost, Anguilla japonica - Zuo, Chenpeng; Lyu, Likang; Zou, Wenhui; Wen, Haishen; Li, Yun; Qi, Xin (Frontiers in Endocrinology, 2022)
Neurokinin B (NKB), a member of the tachykinin (TAC) family, plays important roles in mammalian neuropeptide secretion in related to reproduction. However, its potential role in spawning migration teleost is less clear. In the present study, Japanese eel (Anguilla japonica) was employed to study the performance of NKB in regulating reproduction. Results showed that two tac3 and one tacr3 genes were identified in Japanese eel. Sequence analysis showed that two tac3 transcripts, tac3a and tac3b, encode four NKBs: NKBa-13, NKBa-10, NKBb-13, and NKBb-10. However, compared with other species, a mutation caused early termination of TACR3 protein was confirmed, leading to the loss of the 35 amino acid (aa) C-terminal of the receptor. Expression analysis in different tissues showed that both tac3a and tac3b mRNAs were highly expressed in the brain. In situ hybridization localized both tac3a and tac3b mRNAs to several brain regions, mainly in the telencephalon and hypothalamus. Because of the mutation in TACR3 of Japanese eel, we further analyzed whether it could activate the downstream signaling pathway. Luciferase assay results showed the negative regulation of cAMP Response Element (CRE) and Sterol Response Element (SRE) signal pathways by Japanese eel NKBs. Intraperitoneal injection of four different NKB mature peptides at 100 ng/g had negative effect on either gnrh or gth gene expression. However, the high concentration of NKBa-10 and NKBb-13 (1,000 ng/g) upregulated mgnrh and fshb or lhb expression level significantly, which may be mediated by other receptors. In general, the NKBs/NK3Rs system has important functions in regulating eel puberty onset.